Reported health, social support, stress and associations with choline intake in pregnant women in central South Africa: the NuEMI study 2018-2019 - Liska Robb; Elizabeth Margaretha Jordaan; Gina Joubert; Jennifer Ngounda; Corinna May Walsh (BMC, 2023)
Abstract Background The health and well-being of pregnant women can influence pregnancy outcomes and are closely associated with social support and experiences of stress. Poor nutrition predisposes to poor health with choline intake affecting pregnancy outcome. This study determined reported health, social support, and stress and how these factors are associated with choline intake in pregnancy. Methods A cross sectional study was performed. Pregnant women in their second and third trimesters attending a high-risk antenatal clinic at a regional hospital in Bloemfontein, South Africa, were included. Trained fieldworkers obtained information during structured interviews using standardised questionnaires. Logistic regression with backward selection (p < 0.05) was used to select significant independent factors associated with choline intake. Variables with a p-value < 0.15 in bivariate analysis were considered for inclusion in the model. Results Median age and gestation in the sample (N = 682) were 31.8 years and 32.0 weeks, respectively. Most participants (84.7%) consumed less than the adequate intake (AI) of 450 mg of choline per day. Most participants (69.0%) were either overweight or obese. One in eight participants (12.6%) reported not having anyone that could help them in times of need, more than one third (36.0%) reported having unpayable debt and one in twelve (8.4%) reported experiencing physical abuse by their partners. Normotensive participants and those using anti-retroviral therapy (ART) (thus HIV-infected), were more likely to consume choline in amounts below the AI (p = 0.042 and p = 0.011, respectively). Logistic regression analysis showed that the odds of consuming choline in amounts below the AI were lower for participants that were not using ART versus those using ART, with an odds ratio of 0.53. Conclusion HIV-infected participants were more likely to consume choline in levels below the AI. This vulnerable group should be the focus of targeted efforts to improve choline intake.